Devastation of Earth: an Ecocriticism Study in Cormac McCarthy’s The Road - FAHMI LEKSONO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Abstrak Karya sastra merupakan miniatur dari dunia nyata, dimana sebuah karya sastra biasanya mengungkap beberapa masalah yang berkaitan dengan makhluk hidup termasuk isu-isu tentang hubungan manusia dengan alam. Manusia lebih cenderung melakukan kerusakan pada lingkungan daripada menjaganya, hal ini menyebabkan kehancuran bumi beserta isinya. Hal ini tergambar pada novel The Road karya McCarthy dimana lingkungan yang menjadi setting utamanya hancur berantakan. Lansekapnya tertutup oleh abu yang berterbangan. Dan ketika salju turun, ia berwarna abu-abu. Langitnya juga terlihat gelap. Oleh sebab itu, ada beberapa masalah yang berhubungan dengan kehancuran bumi yang tergambar pada novel yang kemudian memunculkan dua dasar pertanyaan (1) bagaimana kehancuran bumi digambarkan dalam novel The Road karya McCarthy? Dan (2) bagaimana kehancuran bumi memberikan dampak terhadap karakter utama dalam novel The Road karya McCarthy?. Untuk melihat masalah ini perlu teori yang pas yang biasa disebut ecocriticism. Ecocriticism melihat kehancuran bumi sebagai hasil dari tingkah laku manusia terhadap lingkungan misalnya: eksploitasi dan colonialisasi. Seperti yang dikatakan Lawrence Buell bahwa kondisi lingkungan itu ditentukan oleh manusia. Ecocriticism adalah suatu istilah yang berada dibawah payung postcolonialism dimana seorang postcolonialist meyakini bahwa kolonialisasi mempunyai campur tangan dalam penghancuran bumi. Para penjajah merasa percaya diri untuk mengeksploitasi bumi karena dianugrahi kekuatan oleh modernism. Untuk mendapatkan analisis yang jelas, skripsi ini menggunakan metode descriptive quality dimana kualitas data menjadi poin utama daripada jumlah data. Jadi, terlihat jelas bahwa kehancuran bumi terjadi diseluruh lapisan lingkungan; yaitu atmosfer, permukaan tanah, dan laut. Seluruh atmosfer dipenuhi oleh abu, debu dan karbon, tanahnya terkikis, tandus dan gundul, dan lautnya berubah menjadi abu-abu. Kehancuran bumi ini juga memberikan kesuraman tersendiri kepada tokoh si bapak dan si anak. Mereka harus melalui hidup yang keras, susah untuk bernafas, susah untuk menemukan sesuatu yang bisa dimakan dan secara mental mereka selalu takut akan ancaman-ancaman dari kehancuran bumi. Kata Kunci: kehancuran bumi, ecocriticism, postcolonialism, modernism. Abstract Literary work is a miniature of larger world or reality, whereas a literary work reveals some problems related to humans being including issues of human relationships with the environment. Humans tend to do damage to the environment rather than maintaining it, thus it causes devastation of earth. It is reflected in McCarthy’s the road where the environment is devastated. The landscape save the ash on the wind, and when the snow falls, it is gray. The sky is also dark. Therefore, there are some problems of knowledge about how the devastation of earth portrays in the novel, which are delivered to two main questions of (1) How is devastation of earth depicted in Cormac McCarthy’s The Road? and (2) How does devastation of earth give impacts to the main characters in Cormac McCarthy’s The Road?. In case to observe these problems, it needs a suitable theory which called ecocriticism. Ecocriticism sees the devastation of earth as the result of humans’ behaviour such as exploitation and colonialism of the environment, as Lawrence Buell says that the condition of the environment is determined by humans. Ecocriticism is under umbrella term of postcolonialism in which postcolonilist believes that colonization has intervention in devastating the earth. Colonizer is encouraged to exploit the nature because of power that is given by modernism. To get a clear analysis, this thesis uses descriptive quality method; it means the quality of the data becomes the reference to work rather than the quantity of the data. Thus, it is seen clearly that devastation of earth happened in the whole layers of environment; atmosphere, land and sea. The atmosphere is occupied by ash, dust and carbon, the land has eroded and barren and the sea have changed into gray. This devastation also gives a misery to the father and the son as the main characters. They have to undergo hard life; hard to breathe, hard to find food and mentally they are haunted by the devastated earth’s threatens. Keywords: devastation of earth, ecocriticism, postcolonialism, modernism. INTRODUCTION Humans often feel indifferent toward nature. For them, nature is something considerably as a ‘mystic’ thing, when it goes right, humans forget it, when it goes wrong, they worry it. People tend to prefer natural environments more than built environments, and built environments with water, trees, and other vegetation more than built environments without such features (Kaplan & Kaplan, 1989). On the other word, humans tend to permit the nature walks down by itself. They seem to just let it flow without thinking how to keep and maintenance the nature. The study of humans’ relation with nature which is known as ecology was begun since years ago when humans lived in harmony with the nature. However, in line with development the nature also changes. Unfortunately, this natural changes brings devastation on earth, as Donald Hughes says that looking back to our historical ecology, Humans have related in multiple ways to the Earth’s systems; some of these ways promise a sustainable balance with them, while others are destructive (Hughes, 2001: 269). Historically, through devastation of earth Humans have made major changes in their environments. This is happened almost in the whole surface, as Hughes says that devastation of earth has happened in every historical period and in every part of the inhabited Earth (2001: 1). In order to observe those processes of change that affect the relationship, ecologist studies the mutual effects that other species, natural forces, and cycles have on humans, and the actions of humans that affect the web of connections with non-human organisms and entities (id. at 4.). This ecologist’s study shows that devastation of earth is the result of humans’ behaviour toward environment. This bad behaviour has changed the environment that will bring devastation to the humans themselves. Humans seemingly don’t care of the environment. Severity, humans tend to be more destructive. It forces some Ecocritics who concern in literary study and environment in late nineteenth criticized humans’ behaviour toward nature. This criticises show how important avoiding that kind of behaviour toward nature which brings devastation of earth merely, it signed that the study of literature which related to the environment has to be discussed. There were in fact some isolated calls for an ecologically oriented criticism during the 1970s (Rigby, vol 2: 2). However, it was not until the end of the twentieth century that the study of literature and the environment was finally recognized as ‘a subject on the rise’. In studying of literature, humans ordinarily focus on the relation between humans and others (society) or between humans and themselves (psychology), whereas, the relation between humans and environment actually is tightly connected. Unfortunately, the study of literature which related to the earth was often forgotten, whereas, the study of literature which related to the environment is greatly important. The study of environment is not merely observing of the nature or nonhumans aspect but it tends to study the relation among nature, earth and the humans themselves. Human actually is a part of environmental system, and therefore the environment has the crucial role in humans life in which it is become the main point of literary study. In some respects, it is perhaps not surprising that the study of literary texts should be coupled with such forgetfulness of the earth. Thus it is needed a study of humans’ relation and environment. The study of literature and environment got a full attention when modern era begun to destruct the environment. Since last decade ago, especially years ago, humans consciously realized the impacts of their behaviour toward nature, moreover when they become crazier of invention, exploration and exploitation of the nature. Surely, this impact is indirectly causing ecological changes. However, actually what people do about their ecology depend on what they think about themselves in relation to things around them. Human ecology is deeply conditioned by beliefs about our nature and destiny (White 1996, 6). It can be imagined when humans were only thinking about themselves and forgetting the nature or they were just considering their needs without considering the nature needs, it can be ascertained that the nature will vanish and be extinct. This idea or thought about indifference toward nature is criticized by the Ecocritics. Ecocriticism maintains that literature may be approached in a way that examines humans as part of an ecosystem; they are neither master nor slave to it, but simply one part of an intricate system. Literature and environment truly can’t be separated each other. Moreover, Lawrence Buell argues in his book The Truth of Ecology as quoted by Dana Philip that literature would be environmental. It would evoke the natural world through verbal surrogates, and would thereby attempt to bond the reader to the world as well as to discourse (Philip, 2003: 7). It can be assumed that through the literary work, the reader will be brought to the environmental world and devastation of earth. Indirectly, literature causes the reader’s interpretation of the environment. Thus, it is important to understand the relation between humans and environment through literary work. It needs to notice that ecology is not a slush fund of fact, value, and metaphor, but a less than fully coherent field with a very checkered past and a fairly uncertain future (Philip, 2003: 45). By understanding the relation between humans and environment, it is beneficial to determine the act effectively on the impact of natural destruction and to integrate knowledge and actions. The study of literature and environment works in tandem in determining humans’ perception and interpretation toward nature. As Lawrence Buell says that literature and environment studies must make their case for the indispensableness of physical environment as a shaping force in human art and experience, and how such an aesthetic works (2001: 9). It can be assumed that environmental interpretation is a humanistic inquiry. In other word, what people think about nature, and how they have expressed those ideas is what people interpret of the nature. Generally what people expressed the idea of the nature is a Realistic depiction of the world. Thus, it needs a tool to see this depiction. Surely Ecocriticism is a proper tool to see the depiction of the world. Ecocriticism is the most suitable binoculars to telescoped ecological issue and ecological changes in such literary work, as Sheryl Glotfelty (1996: xviii) says that Ecocriticism is the study of the relationship between literature and the physical environment, Ecocriticism takes an earth-centered approach to literary studies. Only Ecocriticicism observes the relation between humans and nonhumans aspects. What Ecocritics do, in short, is attempting to discover nature as absence, silence in texts, and construe environmental representation as a relevant category of literary (Buell, 2005: 30). Ecocriticism encourages the changing of canonisation through entering literary works which carry up natural issue. Ecocriticism ecologically oriented critique of the way in which Nature is constructed in certain canonical texts. Environmental literature constitutes the third way in which Ecocriticism recasts the canon. According to Lawrence Buell (1995, 7-8), an environmentally oriented work should display some characteristics; first, the nonhuman environment is present not merely as a framing device but as a presence that begins to suggest that human history is implicated in natural history. Second, the human interest is not understood to be the only legitimate interest. Third, Human accountability to the environment is part of the text’s ethical framework. The last, some sense of the environment as a process rather than as a constant or a given is at least implicit in the text. In such literary work; Cormac McCarthy’s The Road the nature as the setting represents ecological changes. Surely, this change causes devastation of earth. Nothing is more miserable on earth but devastation. The world which is the closest place we live at is not convenient again when it was devastated. Thus, literary and environment has interrelation that cannot be separated. Then, it is important to analyze such literary work through Ecocriticism. Ecological issue commonly represented by the presence of natural thing such as; tree, land and also circumstance in the novel which it become the setting. In other word, ecological issue become a centre point of setting. One of great writers in narrating the setting is Cormac McCarthy. Not only known as a king of the setting, McCarthy also has known as famous environmental setting as Addy Haddock (a writer of McCarthy’s bibliography) says that his ability to provide eloquent descriptions with smoothly rolling darker undertones and poetically dismal nuances makes him become a writer with powerful setting. Thus, McCarthy is a right author referenced as a study of Ecocriticism. Indirectly, McCarthy’s proficient is caused by his settled at a barn near Louisville, Tennessee. All the stones he gathered, all the wood he cut and kiln dried by himself to renovate his small house. Seemingly, McCarthy’s life is not far away from the nature. Years later, after marrying fellow student Lee Holleman in 1961, he and she moved to a shack with no heat and running water in the foothills of the Smoky Mountains outside of Knoxville. These experiences of life sharpen his idea toward nature. McCarthy reveals that he is not a fan of authors who do not deal with issues of life and death; it can be assumed that his writing tends to be explored issues of life including devastation of earth. Recalling blithely the months he spent without electricity in a house in Tennessee. Without money, and he had run out of toothpaste and he was wondering what to do when he went to the mailbox and there was a free sample. It made him become more sensitive facing the nature and more respect it. In 2006, McCarthy writes The Road that grants him a change to be interviewed by Oprah Winfrey. Surely, this interview related to his writing especially devastation of earth and won Pulitzer Prize for fiction. McCarthy told Winfrey that related several stories illustrating the degree of outright poverty he endured at times during his career as a writer. He also states that his novel; The Road inspired when he was standing at the window of a hotel in the middle of the night, his son asleep nearby, he started to imagine what El Paso might look like 50 or 100 years in the future. He just had this image of these fires up on the hill. It shows the condition of the nature at the time which the hill was fired up. McCarthy can be categorized as a weird person. People usually gathered with other people who have same hobby or pleasure. However, it doesn’t apply for McCarthy. As a writer, he doesn’t like to gather with other writer. He would rather hang out with physicists or scientist than other writer. He does not know any writers and much prefers the company of scientists. No doubt if his knowledge of nature is rich. His knowledge of the natural world is vast and includes many of the Latin names of birds and animals. His pleasure gathering with physicists and scientist caused by his interest in science and environment, by absorbing the intelligence scientists, he realizes that in 100 years the human race won't even be recognizable. For him, what physicists did in the 20th century was one of the extraordinary flowerings ever in the human enterprise, which would much prefer to befriend a scientist than another writer. Most of McCarthy’s novels are portraying about life or reality which many of them associated to ecological issue. In 1985, Blood Meridian was published. Blood Meridian portrays the desolate and indifferent 1850s Texas-Mexico borderlands. The extreme violence which takes place comments implicitly on both the environment and human nature. The novel’s full title- Blood Meridian, or The Evening Redness In The West- is indicative of the novel’s portrayal of the environment. A relationship between location, nature and violence is created in the symbolism of the sun as a “blood meridian”. To call McCarthy’s environments as constructed in Blood Meridian simply violent is an unsatisfactory conclusion. What is more appropriate and evident in the text is that man is inherently violent and the indifference of nature to this creates an amoral setting. In 1979, McCarthy published his fourth novel, Suttree. In short, Suttree tells the reader about a man named Cornelius Suttree, a fisherman, disillusioned scholar, alcoholic, nihilist, existentialist and transcendentalist. The attention to detail identified earlier in Suttree is telling in terms of his relationship with his environment. Generally, to an Ecocritical reading Suttree shows that, stripped of societal anthropocentrism, man is forced to reassess his relationship with nature. It could be said that McCarthy’s prose style is often atavistic (anti-civilization, anti-materialism, anti-industrialism, anti-progress and pro-Nature) in that it both reflects natural processes and often appears primitive, stripped of culture. In 1973, Child of God was published. It was inspired by actual events in Sevier County. Child of God begins with Lester Ballard’s dispossession from his parent’s house. McCarthy’s description of Ballard’s lone nomadic wandering after he inadvertently burns down his squat uses the same free indirect discourse. Child of God can also be described as an existential text, particularly for the authenticity of its protagonist. Lester Ballard’s atavistic tendencies bring him closer to an animalistic level. From those all of McCarthy’s novels, The Road which was published in 2006 by Vintage book publisher is the most representative novel which is related to the study of Ecocriticism. The novel is generally thick of environments’ issue. The issue for instance is the fire of woods that happened along the country which give the reader an image of burned land, ash and dust everywhere and so on. Because of this reason, the writer felt that The Road is interested to be analyzed through ecological critics. In short, the novel portrays a journey of father and son as the main character in a burned land in America. The issue of devastation of earth becomes the centre point of interest which grasps the whole setting of the novel. The Road brings the readers onto ‘the future’ in as much as it is set in a time after an ambiguous ‘end’ has occurred and society has collapsed. The reverse of the most recent reissue claims that it is the first great masterpiece of the globally warmed generation. It is also the first of McCarthy’s novels to have provoked Ecocritical study. This wide appeal to the novel relies strongly on its environmental themes. The use of allusion to genre and form elsewhere in McCarthy’s novels can be said to universalise his appeal but in The Road the key concern is the 21st century’s most immediate global problem; the irrevocable damage global industrial capitalism is doing to our environment. It is difficult to read The Road without feeling the overwhelming cumulative force of the novel’s desolation, and this desolation is most prominently present in the landscapes McCarthy portrays. The setting is almost entirely bereft of life; the little that is found is often malign humanity. The Road greatly represents a study of Ecocriticism. It portrays the colourless world because of devastation of earth. This devastation issue is common object of the Ecocriticism study. The Road continually reminds us of the bleakness of the landscape in the earth. As readers, we only experience bright colours through the characters' dreams or memories, if someone happens to bruise or bleed, or through fire or flare guns. The rest of the time we see a gray ash covering the landscape. As a reality, our landscape is actually green and natural. However, The Road shows the possibility of devastation of earth when humans did devastation to the nature and they can’t live in harmony with the nature. Therefore, there is no doubt that The Road becomes the most influencing novel toward environment. It proves from the acclaim written in the novel by George Monbiot, an environmental campaigner that says